University Curricula in Evidence-Informed Decision Making and Knowledge Translation: Integrating Best Practice, Innovation, and Experience for Effective Teaching and Learning - Jessani, Nasreen S.; Hendricks, Lynn; Nicol, Liesl; Young, Taryn (Frontiers in Public Health, 2019)
As attention to Evidence Informed Decision Making (EIDM) and Knowledge Translation (KT) in research, policy and practice grows, so does a need for capacity enhancement in amongst evidence producers and evidence users. Recognizing that most researchers enter the professional sphere with little or no appreciation of the importance and power of EIDM, the Centre for Evidence-based Health Care at Stellenbosch University, South Africa, spearheaded the development and accreditation of a foundational course titled Evidence-Informed Decision making: The Art, Science and Complexity of knowledge translation. The curriculum draws on the principles of adult learning and effective teaching that includes integrating seven key aspects: 1) extraction of intuitive and tacit knowledge 2) autonomous knowledge generation 3) diverse perspectives 4) learning by doing 5) peer-support and critique 6) facilitator coaching and 7) constant reflection. In this paper we reflect on these techniques in enhancing understanding and utilization of KT in advancing EIDM. The in-person short course has been offered 5 times since its launch in September 2017 with attendance by approximately 85 senior researchers and government officials - each of whom left the workshop with three completed outputs: a stakeholder matrix, an engagement strategy for their chosen stakeholder and a plan for evaluating the impact of their KT strategy. Interest in the course has grown considerably: a) Requests from local institutes of research for dedicated training to their staff; b) Incorporation into international program partner capacity enhancing strategies; c) Publication of a book chapter designed using course content; d) Adaptation and utilization of the templates and tools as teaching resources e) Informing organizational stakeholder engagement strategies f) Adaptation of the modules for conference capacity building workshops. In summary, designing courses that take into consideration adult principles of learning is not a new concept. However, effective delivery of such courses is still nascent. We found that integrating the seven aspects mentioned above, including researchers together with decision-makers in the workshops, and having an experienced facilitator is critical for effective learning. Enhancing knowledge and skills “just in time” rather than “just in case” has demonstrated increased potential for immediate relevance, uptake and sustainability.